Aggregatibacter Actinomycemcomitans Pneumonia in Children: Two Case Reports and a Review of the Literature. Issue 1 (January 2015) - Shilo, Smadar; Kassis, Imad; Hakim, Fahed; Shachor-Meyouhas, Yael
Abstract : Aggregatibacter actinomycemcomitans, previously named Actinobacillus actinomycetemcomitans (Aa), is a facultative Gram-negative slow-growing coccobacillus associated with severe oral and nonoral infections. It is a member of the HACEK group. Pulmonary infection caused by Aa is rare. We describe two cases of Aa pneumonia mimicking malignancy and review published pediatric cases.